The Effect Of Giving Reading Recording Assignments Via Whatsapp Voice Notes On Students' Reading Skills Class 2 SDN Cirengit - Farihiyah Farihiyah; Mia Agustina Nurhadiati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Reading skills refer to an individual's ability to read text accurately and understand its meaning. This study aims to analyze the relationship between the intensity of Voice Note feature use on the WhatsApp application with reading skill indicators, which include articulation, intonation, phrases, and punctuation. In addition, this study also evaluates the effect of giving reading recording assignments via WhatsApp Voice Notes on the reading skills of second-grade students. Using a quantitative approach with a one-shot case study pre-experimental design, this study involved 28 second-grade students at Cirengit Elementary School. Data were obtained through reading aloud tests and WhatsApp Voice Note recordings, then analyzed using descriptive statistics (mean, percentage, and standard deviation) and inferential statistics (Shapiro-Wilk normality test, Pearson and Spearman's Rho correlation, linearity test, and simple linear regression). The results of the analysis indicate that the intensity of WhatsApp Voice Note use has a strong relationship with intonation, phrases, and punctuation use (high category), and a moderate relationship with articulation. Furthermore, the regression results showed that providing reading recording assignments via WhatsApp Voice Notes contributed 49% to improving students' reading skills, with an R-square value of 0.488. This finding confirms that the use of WhatsApp Voice Notes is effective in supporting the improvement of students' reading skills, although the impact varies across indicators.